2018
DOI: 10.1016/j.neuroimage.2016.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Individualized parcellation of the subthalamic nucleus in patients with Parkinson's disease with 7T MRI

Abstract: Deep brain stimulation of the subthalamic nucleus (STN) is a widely performed surgical treatment for patients with Parkinson’s disease. The goal of the surgery is to place an electrode centered in the motor region of the STN while lowering the effects of electrical stimulation on the non-motor regions. However, distinguishing the motor region from the neighboring associative and limbic areas in individual patients using imaging modalities was until recently difficult to obtain in vivo. Here, using ultra-high f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
148
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 118 publications
(163 citation statements)
references
References 41 publications
7
148
0
Order By: Relevance
“…Similarly to the 7 T manual ground truth, the 7 T-ML based STN accurately localized and predicted the active contacts, especially in the posterior lateral region that is considered a motor territory often targeted for Parkinson’s DBS (Plantinga et al, 2016). We should stress that we analyzed the spatial relationship between contact location and the STN using the ellipsoid representation within the STN in an individual patient data space.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly to the 7 T manual ground truth, the 7 T-ML based STN accurately localized and predicted the active contacts, especially in the posterior lateral region that is considered a motor territory often targeted for Parkinson’s DBS (Plantinga et al, 2016). We should stress that we analyzed the spatial relationship between contact location and the STN using the ellipsoid representation within the STN in an individual patient data space.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, 7 T MRI has already facilitated the study of connectivity within the basal ganglia and thalamus and enabled the subdivision of the STN into motor, associative, and limbic sub-regions (Abosch et al, 2010; Lenglet et al, 2012; Plantinga et al, 2016). Keuken et al (2013) investigated structural changes of the STN using atlases based on 7 T MRI in different age groups (healthy subjects).…”
Section: Introductionmentioning
confidence: 99%
“…Shih et al (2011) identified three functional subdivisions in the pSTS using a data-driven approach. Furthermore, research at a fine-grained level may help in more accurately positioning the abnormal subarea of the pSTS in patients with conditions such as simultanagnosia or ASD (Jaimes et al, 2017;Plantinga et al, 2018). Comparing the two different parcellation schemes, the distribution of the subareas and the direction of the boundary are basically analogous.…”
Section: Discussionmentioning
confidence: 99%
“…These advanced techniques allow for detailed delineation of the connections between the STN (and GPi), cortex and other basal ganglia structures at the individual patient level. Several studies in healthy adults have demonstrated how the STN subsections and overlaps can be delineated using tractography [1], [2], [34], [51]. Implementing state-of-the-art tractography methods, combined with VTA-modeling, may allow detailed exploration of the neural pathways stimulated with DBS in individual patients.…”
Section: Directions For Future Researchmentioning
confidence: 99%